GOVERNMENT LEADERSHIP COMPETENCE IN THE FORMULATION OF PROGRESSIVE PUBLIC POLICIES (Study of Regional Leadership in Bandar Lampung) - eko budi sulistio (Universitas Muhammadiyah Lampung, 2021)
Public Policy is one of the keys to success in implementing governance and development, both at the national and local (regional) level. Progressive public policy will determine the direction of development policy in the future. Public policy is determined by many actors both government and non-government. However, government actors have a very dominant role. At the local level, the regional head becomes a barometer of how the quality of public policy is produced. This study intends to analyze the competence of regional heads in the formulation of progressive public policies in Bandar Lampung, especially in the field of infrastructure. Keywords: Government, Leadership, Public Policies